PEMANFAATAN MEDIA ONLINE UNTUK MELESTARIKAN BUDAYA TRADISIONAL: Studi Deskriptif Kualitatif Pada Lembaga Balai Kajian dan Pengembangan Budaya Melayu (BKPBM) Yogyakarta dalam Melestarikan Budaya Melayu - Najib (Indra institute Research & Publication, 2024)
This study aims to determine how the use of the website by the Institute for the Study and Development of Malay Culture in Yogyakarta in developing and preserving Malay culture and what factors support and hinder the method. The type of research conducted is qualitative research, namely research that is systematic, directed and accountable, so that it does not lose its scientific nature. Data collection techniques used are observation, document review, and interviews. The results showed that the use of the website as an effort to develop and preserve Malay culture had a significant positive impact. The information submitted on the website is in detail so that this is evidence of a comprehensive, systematic and accurate value because the use of the website is supported by a large capacity in delivering messages. In addition, offline activities are also a supporting factor so that websites are easily recognized. While the inhibiting factor is that the budget owned by the Malay Cultural Studies and Development Center as a private institution is not comparable to the high operational costs, especially the website and this also has an impact on the lack of Human Resources as managers. In addition, Mahyudin Al-Mudra's health is declining as the head of the institution.